2020
DOI: 10.1161/circheartfailure.120.007154
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparities in the Management and Outcomes of Cardiogenic Shock Complicating Acute Myocardial Infarction in the Young

Abstract: Background: There are limited data on how sex influences the outcomes of acute myocardial infarction-cardiogenic shock (AMI-CS) in young adults. Methods: A retrospective cohort of AMI-CS admissions aged 18 to 55 years, during 2000 to 2017, was identified using the National Inpatient Sample. Use of coronary angiography, percutaneous coronary intervention, mechanical circulatory support and noncardiac interventions was identified. Outcomes of interest inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(40 citation statements)
references
References 46 publications
1
37
2
Order By: Relevance
“…Demographic characteristics including age, sex, race, hospital characteristics, acute organ failure, MCS, cardiac procedures, and non-cardiac organ support therapies were identified for all admissions using previously used methodologies from our group ( Supplementary Table 1 ). 1 , 2 , 3 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 …”
Section: Methodsmentioning
confidence: 99%
“…Demographic characteristics including age, sex, race, hospital characteristics, acute organ failure, MCS, cardiac procedures, and non-cardiac organ support therapies were identified for all admissions using previously used methodologies from our group ( Supplementary Table 1 ). 1 , 2 , 3 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 …”
Section: Methodsmentioning
confidence: 99%
“…Female sex remained an independent predictor of higher in-hospital mortality (adjusted OR 1.05; 95%CI: 1.02-1.08; P < 0.001)[ 8 ]. Similarly, NIS data for younger patients (18-55 years) also showed that women experienced higher hospital mortality, and that female sex was an independent predictor of in-hospital mortality (adjusted OR 1.11, 95%CI: 1.07-1.16; P < 0.001)[ 17 ] (Figure 1 ). The timely use of reperfusion strategies could potentially improve survival among women.…”
Section: Sex Disparity In Outcomesmentioning
confidence: 94%
“…These findings have also been observed even among younger patients. An analysis of the National Inpatient Sample (NIS) (the largest inpatient administrative database in the United States) of AMI complicated by cardiogenic shock admissions aged 18-55 years, between 2000 to 2017, found that younger women also tend to have higher burden of comorbidities[ 17 ]. Table 1 summarizes the studies comparing the prevalence and risk profile between women and men.…”
Section: Sex Differences In the Prevalence And Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in-hospital mortality is higher amongst Hispanics (74%) and African Americans (65%), these differences disappear when controlled for access to primary PCI ( 20 ). Similarly, the higher mortality observed amongst women with AMI-CS ( 21 ), is reduced with the use of standardized management algorithms ( 22 ).…”
Section: Current Landscapementioning
confidence: 99%